2016
DOI: 10.3390/ijerph13030276
|View full text |Cite
|
Sign up to set email alerts
|

Backcountry Travel Emergencies in Arctic Canada: A Pilot Study in Public Health Surveillance

Abstract: Residents in the Canadian Arctic regularly travel in remote, backcountry areas. This can pose risks for injuries and death, and create challenges for emergency responders and health systems. We aimed to describe the extent and characteristics of media-reported backcountry travel emergencies in two Northern Canadian territories (Nunavut and Northwest Territories). A case-series of all known incidents between 2004 and 2013 was established by identifying events in an online search of two media outlets, Nunatsiaq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Many changing climate conditions and resultant environmental impacts nega tively affect individual and community health and wellbeing in rural and remote regions, including: increased prevalence and severity of extreme weather events; 1,2,5,1012 changes to sea ice, vegetation, fish, wild life, and water; 1,2,5,12,13 and weather and environmental uncertainties. 1,2,6,14 Negative health outcomes associated with these changes include an increased preva lence of poor nutrition, obesity, and dia betes; 5,15,16 vectorborne, waterborne, and foodborne disease; 5,12,16,17 cardiovascular dis ease; 15,16 respiratory issues; 18 injury and mortality; 1214 and mental health issues. 3,6,1820 Characteristics of rural and remote regions may increase the sensitivity to these health risks, such as remote geography and limited transportation infrastructure, reliance on natural resources, and under resourced social and physical infrastruc ture.…”
Section: Climate Change Health and Wellbeing In Rural And Remote Rementioning
confidence: 99%
“…Many changing climate conditions and resultant environmental impacts nega tively affect individual and community health and wellbeing in rural and remote regions, including: increased prevalence and severity of extreme weather events; 1,2,5,1012 changes to sea ice, vegetation, fish, wild life, and water; 1,2,5,12,13 and weather and environmental uncertainties. 1,2,6,14 Negative health outcomes associated with these changes include an increased preva lence of poor nutrition, obesity, and dia betes; 5,15,16 vectorborne, waterborne, and foodborne disease; 5,12,16,17 cardiovascular dis ease; 15,16 respiratory issues; 18 injury and mortality; 1214 and mental health issues. 3,6,1820 Characteristics of rural and remote regions may increase the sensitivity to these health risks, such as remote geography and limited transportation infrastructure, reliance on natural resources, and under resourced social and physical infrastruc ture.…”
Section: Climate Change Health and Wellbeing In Rural And Remote Rementioning
confidence: 99%
“…Residents in Inuvik identified risk factors for boating incidents in the community as gender, age, place, lack of enforcement, and a lack of knowledge and preparation. While the factors of gender (Giles et al, 2013;Jardine et al, 2009), age (Giles et al, 2013), and place (Young et al, 2016;Durkalec et al, 2014) have been previously identified as important to understanding risktaking behaviours in northern Canada, these factors have not been considered in combination with each other, or through the perspective of northern Aboriginal men.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the participants identified four main risk factors that male residents of Inuvik believed to be associated with men's boating incidents in Inuvik, NWT: gender, age, place, and lack of enforcement, knowledge and preparation. While the risk factors of gender (Giles et al, 2013;Jardine et al, 2009), age (Giles et al, 2013), and place (Young et al, 2016;Durkalec et al, 2014) have been previously identified by researchers as being important in terms of understanding risk-taking behaviours in northern Canada, these factors have not been assessed together in a specific community and cultural context, in relation to boating safety, and through a postcolonial feminist lens. Importantly, understanding the specific risk factors from Aboriginal men's perspectives may lead to health promotion or injury prevention activities that are culturally safe and thus more effective for residents.…”
Section: Discussionmentioning
confidence: 99%
“…Les changements climatiques ont de ce fait des effets à la fois directs et indirects sur la santé et le bien-être des individus et des collectivités 1,2,5,7,8 . 1,2,5,[10][11][12] , la modification des glaces maritimes, de la végétation, des espèces de poisson, de la faune en général et de l'eau 1,2,5,12,13 ainsi que des incertitudes quant au climat et à l'environnement 1,2,6,14 .…”
Section: Introductionunclassified
“…Les principaux effets nocifs pour la santé associés à ces changements sont une incidence accrue de la malnutrition, de l'obésité et du diabète 5,15,16 , des maladies à transmission vectorielle ou d'origine hydrique ou alimentaire 5, 12,16,17 , des maladies cardiovasculaires 15,16 , des troubles respiratoires 18 , des blessures et des décès [12][13][14] et des problèmes de santé mentale 18,19 .…”
Section: Introductionunclassified